2020
DOI: 10.1159/000508922
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes in Biopsy Specimens Obtained 7 Days after Starting Chemoradiotherapy for Rectal Cancer Are Predictors of the Response to Chemoradiotherapy

Abstract: <b><i>Background:</i></b> Neoadjuvant chemoradiotherapy (nCRT) followed by total mesorectal excision surgery is a standard treatment for locally advanced rectal cancer (LARC). Tumor-infiltrating lymphocytes (TILs) have been reported to be associated with tumor response; however, this remains to be established. We previously reported that histological changes on biopsy specimens obtained 7 days after starting nCRT are strong predictors of response to nCRT. <b><i>Methods:</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The potential of using TILs in preoperative prognostication to predict response to neoadjuvant therapy can be a valuable step towards personalized treatment. In some cancers, biopsies have been successfully used to assess TILs as a predictor of treatment response [69][70][71] and to predict lymph node metastasis [72]. Similar studies in preoperative HNSCC biopsies are warranted.…”
Section: Why Is the Assessment Of Tils Not Yet Used In The Daily Prac...mentioning
confidence: 99%
“…The potential of using TILs in preoperative prognostication to predict response to neoadjuvant therapy can be a valuable step towards personalized treatment. In some cancers, biopsies have been successfully used to assess TILs as a predictor of treatment response [69][70][71] and to predict lymph node metastasis [72]. Similar studies in preoperative HNSCC biopsies are warranted.…”
Section: Why Is the Assessment Of Tils Not Yet Used In The Daily Prac...mentioning
confidence: 99%
“…This has also been reported in studies of CRC 10 , 11 , 32–34 . In contrast, other studies have not found a significant correlation between TIL density in pre-operative biopsies and tumor shrinkage after neoadjuvant treatment 12 , 35 . This discrepancy may be due to the different evaluation systems used for TRG, cutoff values set for high and low influx of TILs, size of the cohorts, and/or intracohort dependency in the quantification model.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study no correlation of pretreatment CD8 + TILs and survival was detected, while a decrease in CD8/FoxP3 ratio after treatment predicted better overall and progression-free survival. A more recent study comparing pre-treatment and biopsy material obtained from rectal tumours 7 days after irradiation showed that a high density of CD4 + and FoxP3 + cells pre-treatment was significantly associated with tumour shrinkage, and that this link was most pronounced in the 7 day biopsies [112]. The location of CD8 + and FoxP3 + T cells in relation to each other as well as the distance from the tumour cells (stromal vs intra-tumoural) could reflect functionality.…”
Section: Cd8 + T Cellsmentioning
confidence: 99%